Optimal surgical treatment in patients with T1b gallbladder cancer: An international multicenter study. (18th December 2018) - Kim, Hyeong Seok; Park, Jae Woo; Kim, Hongbeom; Han, Youngmin; Kwon, Wooil; Kim, Sun‐Whe; Hwang, Yoon Jin; Kim, Sang Geol; Kwon, Hyung Jun; Vinuela, Eduardo; Járufe, Nicolas; Roa, Juan Carlos; et al.
Abstract : Highlight Kim and colleagues conducted an international multicenter study to explore the optimal surgical strategy for the treatment of T1b gallbladder cancer in terms of recurrence and disease‐specific survival. They demonstrated that simple cholecystectomy, including laparoscopic cholecystectomy, with or without lymph node dissection yielded similar outcomes to those of extended cholecystectomy. Abstract: Background: There is no consensus on the optimal treatment of T1b gallbladder cancer (GBC) due to the lack of evidence and the difficulty of anatomy and pathological standardization. Methods: A total of 272 patients with T1b GBC who underwent surgical resection at 14 centers with specialized hepatobiliary‐pancreatic surgeons and pathologists in Korea, Japan, Chile, and the United States were studied. Clinical outcomes including disease‐specific survival (DSS) rates according to the types of surgery were analyzed. Results: After excluding patients, the 237 qualifying patients consisted of 90 men and 147 women. Simple cholecystectomy (SC) was performed in 116 patients (48.9%) and extended cholecystectomy (EC) in 121 patients (51.1%). The overall 5‐year DSS was 94.6%, and it was similar between SC and EC patients (93.7% vs. 95.5%, P = 0.496). The 5‐year DSS was similar between SC and EC patients in America (82.3% vs. 100.0%, P = 0.249) as well as in Asia (98.6% vs. 95.2%, P = 0.690). The 5‐year DSS also did not differ according to lymph node metastasis ( P = 0.688) or tumor location ( P = 0.474). Conclusions: SC showed similar clinical outcomes (including recurrence) and survival outcomes as EC; therefore, EC is not needed for the treatment of T1b GBC.